Multiple desmoid tumors in a patient with Gardner's syndrome – Report of a case - Pinheiro, Lílian Vital (Elsevier, 2014)
INTRODUCTION: Desmoid tumor (DT) is a common manifestation of Gardner's Syndrome (GS), although it is a rare condition in the general population. DT in patients with GS is usually located in the abdominal wall and/or intra-abdominal cavity. PRESENTATION OF CASE: We report a case of a 32 years-old female patient with familial adenomatous polyposis (FAP), who was already submitted to total colectomy and developed multiple DT, located in the abdominal wall and in the left breast. The patient underwent several surgical procedures, with a multidisciplinary team of surgeons. Wide surgical resections of the left breast and the abdominal wall tumors were performed in separate steps. Polypropylene mesh reconstruction and muscle flaps were needed to cover the defects of the thoracic and abdominal walls. After partial necrosis of the adipose-cutaneous flap in the abdomen that required a new skin graft, she had a satisfactory outcome with complete healing of the surgical incisions. DISCUSSION: DT is frequent in GS, however, breast localization is very rare, with few cases reported in the literature. Recurrence of DT is not negligible, even after a wide surgical resection. GS patients must be followed up closely, and clinical examination, associated with imaging studies, should be performed to detect any signs of tumor. CONCLUSION: DT represents one of the most significant causes of the morbidity and mortality that affects FAP patients following colectomy. In general, the surgical procedures to excise DT are highly complex, requiring a multidisciplinary team.